Penggunaan sistem maklumat geografi untuk meramal keruntuhan cerun di Pulau Pinang - Ahmad, Fatimah Shafinaz (2005)
Landslide constitutes one of the major hazards that cause losses of lives and properties which require complex analyses involving multitude of factors. The conventional methods to predict landslide are normally time consuming. Geographical Information System (GIS) is an ideal tool for landslide modelling owing to its versatility in handling large set of data, providing an efficient environment for analysis and displaying result using its powerful set of tools for collecting, storing, monitoring, integrating, manipulating, analysing and displaying geographical data (spatial and attribute data) from the real world. There are eight factors that contribute to landslide such as rainfall, water flow, slope, underground water, land use, erosion and mineral. The increasing usage of computer-based tools is found to be useful in hazard mapping of landslides, and GIS is the one of such significant tools. The main advantage of using this technology is the possibility of improving hazard occurrence models by evaluating their results and adjusting the input variables. The unique feature of GIS is the ability to work with data referenced by vast spatial or geographic coordinates. This study is to proof the ability of GIS to present data and analysis results in map forms in identifying the critical area of landslide. The final results from this research are landslide map and user interface.